2018
DOI: 10.14419/ijet.v7i1.9.10013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-pregnancy maternal body mass index on gestational diabetes mellitus

Abstract: The prevalence of both obesity and Gestational Diabetes Mellitus (GDM) is increasing worldwide. Overweight and obesity are abnormal or excessive fat accumulation that presents a risk to health. The presence of obesity has, in particular, a significant impact on both maternal and fetal complications associated with GDM. These complications can be addressed, at least in part, by good glycaemic control during pregnancy. The objective of the study is to classify GDM and non-GDM patients based on pre-pregnancy mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In addition to inflammatory reaction, IR and abnormality of lipid and glucose metabolism, GDM also involves DNA methylation and oxidative stress signal transduction that affect cardiac function (21). Statistics showed that the increase in the prevalence of GDM is global and 33.33% of GDM pregnant women will suffer from postpartum depression (22,23). In order to avoid the possible serious impact of GDM on the health of pregnant women and newborns, we advocate healthy diet and reasonable physical exercise for women during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inflammatory reaction, IR and abnormality of lipid and glucose metabolism, GDM also involves DNA methylation and oxidative stress signal transduction that affect cardiac function (21). Statistics showed that the increase in the prevalence of GDM is global and 33.33% of GDM pregnant women will suffer from postpartum depression (22,23). In order to avoid the possible serious impact of GDM on the health of pregnant women and newborns, we advocate healthy diet and reasonable physical exercise for women during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…4 Women who have presented with GDM show a higher risk of recurrence in future pregnancies and developing type 2 diabetes mellitus (T2DM). 5 GDM is also a risk factor for maternal cardiovascular diseases (CVDs), including coronary artery disease, peripheral vascular disease, and myocardial infarction. Infants of diabetic mothers present metabolic, haematological, and cardiac disorders, respiratory stress, and neurological defects due to perinatal asphyxiation and other birth trauma such as macrosomia.…”
Section: Introductionmentioning
confidence: 99%
“…GDM prevalence in women with pre‐pregnancy obesity was approximately fourfold higher compared with women with pre‐pregnancy normal weight 4 . Women who have presented with GDM show a higher risk of recurrence in future pregnancies and developing type 2 diabetes mellitus (T2DM) 5 . GDM is also a risk factor for maternal cardiovascular diseases (CVDs), including coronary artery disease, peripheral vascular disease, and myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is the most common metabolic disorder of pregnancy (Chiefari et al, 2017), with maternal age and obesity being important risk factors for GDM development (Li et al, 2020). The prevalence of overweight and obesity is rising in women of reproductive age (affecting up to 50%), highly contributing to an augmented prevalence of GDM (Rodrigo & Glastras, 2018; Shirley Muller & Nirmala, 2018). GDM is defined as any degree of glucose intolerance developed in late gestation after clearly dismissing pregestational diabetes.…”
Section: Introductionmentioning
confidence: 99%